Results of the Carillon Procedure in Proportionate and Disproportionate FMR: Effects of the Baseline Echocardiographic Parameters - Piotr Kałmucki; Rafał Dankowski; Janusz Lipiecki; Artur Baszko; Tomasz Siminiak (Journal of Clinical Medicine, 2026)
Background: Transcatheter edge-to-edge repair and percutaneous mitral annuloplasty with the Carillon device are techniques used in the treatment of functional mitral regurgitation (FMR). Both approaches have been shown to have divergent clinical outcomes in patients with proportionately severe and disproportionately severe FMR. Objective: To evaluate which patients could benefit most from percutaneous mitral annuloplasty, we evaluated the possible correlation between echocardiographic parameters at baseline and their change one year after the Carillon procedure in subjects with proportionate versus disproportionate FMR. Methods: We performed a pooled analysis from three trials of patients with FMR. The main inclusion criteria included persistent grades 2+ to 4+ FMR with >5.5 cm left ventricular (LV) end-diastolic diameters (LVEDDs) and a reduced LV ejection fraction. Patients with an effective regurgitant orifice area/LV end-diastolic volume (EROA/LVEDV) ratio equal to 0.15 mm2/mL or less were assigned to the proportionate FMR group (n = 74; 65%), and those with a ratio above 0.15 mm2/mL were classified as having disproportionate FMR (n = 39; 35%). Results: In both groups, the changes in LV systolic and diastolic volumes after the procedure correlate negatively with baseline LV volumes, suggesting larger improvements (decreases) in LV volumes in patients with more pronounced LV dilatation at the baseline. In contrast to the disproportionate group, in patients with proportionate FMR, no correlation between the baseline LV diameters and improvement in LV volumes after 12 months was observed. However, higher baseline LV diameters predicted a higher degree of decrease in LV diameters in “proportionate” but not “disproportionate” FMR patients. Interestingly, the improvement in EF as a result of the Carillon implantation was not predicted by any of the baseline parameters studied. However, in both groups, the 12-month change in mitral annular area negatively correlated with baseline vena contracta but not with RV and EROA. Conclusions: In FMR patients undergoing the Carillon procedure, higher baseline LV volumes may predict more pronounced reverse remodeling, defined as a decrease in LV volumes. Higher values of vena contracta may predict larger reductions in the mitral annular area. High baseline LV diameters could suggest improvements in LV volumes in disproportionate FMR and in LV diameters in proportionate FMR, probably due to different LV geometries.